Blockchain and smart contract for access control in healthcare: A survey, issues and challenges, and open issues. (15th March 2021) - Sookhak, Mehdi; Jabbarpour, Mohammad Reza; Safa, Nader Sohrabi; Yu, F. Richard
Abstract: Emerging technologies are playing a critical role in the evolution of healthcare systems by presenting eHealth to provide high-quality services and better health to wide-range of patients. Achieving the eHealth goals highly depends on employing modern information and communication technologies (ICTs) to securely and efficiently collect and transmit electronic health records (EHRs) and make them accessible to authorized users and healthcare providers. However, the adoption of EHRs in healthcare providers puts the patients' privacy and their information security at risk of data breaches. The advent of smart contracts and blockchain technology paves a way for developing efficient EHR access control methods to support secure identification, authentication, and authorization of the clients. This paper delineates an extensive survey on the state-of-the-art blockchain-based access control methods in healthcare domain as a basis for categorizing the existing and future developments in access control area. A thematic taxonomy of the blockchain-based access control methods is also presented to recognize the security issues of the existing methods and highlight the fundamental security requirements to design a granular access control method. This paper also aims for examining the similarities and differences of the traditional access control methods and describes some substantial and outstanding issues and challenges as further directions.